2015
DOI: 10.1161/atvbaha.114.303411
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Integrin and Integrin Signaling in Treating Thrombosis

Abstract: The critical roles of integrins in thrombosis have enabled the successful development and clinical use of the first generation of integrin antagonists as represented by abciximab (Reopro), eptifibatide (Integrilin), and tirofiban (Aggrastat). These integrin αIIb β3 antagonists are potent anti-thrombotics, but also have significant side effects. In particular, their induction of ligand-induced integrin conformational changes is associated with thrombocytopenia. Increased bleeding risk prevents integrin antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 83 publications
3
123
0
Order By: Relevance
“…Antibodies, disintegrins, and Arg-Gly-Asp sequence analogues with the mode of action have been developed as potent antiplatelet agents [11] and three of them, abciximab, epitifibatide and tirofiban, are clinically available. [12] Despite the clinical efficacy of these antiplatelet agents, severe thrombocytopenia, paradoxical induction of thrombosis, as well as bleeding have been reported as adverse side effects. [11] Several studies have also revealed that binding of such ligand-mimetic compounds results in conformational changes in the extracellular domains of integrin IIb3, which may even induce integrin-dependent downstream signaling.…”
Section: Accepted Articlementioning
confidence: 99%
“…Antibodies, disintegrins, and Arg-Gly-Asp sequence analogues with the mode of action have been developed as potent antiplatelet agents [11] and three of them, abciximab, epitifibatide and tirofiban, are clinically available. [12] Despite the clinical efficacy of these antiplatelet agents, severe thrombocytopenia, paradoxical induction of thrombosis, as well as bleeding have been reported as adverse side effects. [11] Several studies have also revealed that binding of such ligand-mimetic compounds results in conformational changes in the extracellular domains of integrin IIb3, which may even induce integrin-dependent downstream signaling.…”
Section: Accepted Articlementioning
confidence: 99%
“…Integrin a 2 b 1 is a receptor for collagen, but also bind tenascin and the proteoglycan decorin (Guidetti et al, 2002;Schaff et al, 2011), while integrin a IIb b 3 , which is exclusively expressed in platelets, binds several adhesive proteins, including fibrinogen, von Willebrand factor (VWF) and fibronectin (Bennett, 2005;Ruggeri et al, 1999). These integrins are differently involved in specific phases of platelets adhesion, are able to initiate intracellular signaling pathways for platelet activation and are involved in establishing cellecell contact during platelet aggregation and thrombus formation (Estevez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This receptor is expressed in a low-affinity form that does not bind ligand, but after intracellular signaling, it forms a high-affinity ligand-binding site, enabling platelet aggregation and outside-in-signaling to reinforce platelet activation. 28 In addition to αIIbβ3, other platelet integrins, α2β1, α5β1, and α6β1 that bind collagen, fibronectin, or laminin, respectively, also become functional on activated platelets and promote firm platelet adhesion to collagenous subendothelial matrix. 29,30 This amplification of platelet activation through release of secondary agonists is critical in stabilizing the thrombus and augmenting the thrombus volume.…”
Section: Platelet Activation and Thrombus Formation At The Vessel Wallmentioning
confidence: 99%
“…On the basis of recent research discoveries, there is far wider scope for therapeutic regulation of platelet targets, including αIIbβ3, 28,81 integrin α6β1, 82 GPIb-IX-V, and GPVI adhesive function and signaling. In addition to vWF-and GPIbα-targeting inhibitors in development (Table 2), alternative strategies could have advantages, for example, small molecules with increased scope for bioavailability.…”
Section: Future Targets For Antiplatelet Therapymentioning
confidence: 99%